The role of local elites the Philippine experience - Simpas, Santiago S. (1975)
This is an attempt to examine the "role of local elites" in the Philippines and their relevance to rural development. I shall use "elite" interchangeably with "local elites" and "local government officials," especially and exclusively, elective officials at the provincial and lower local government levels. The term "role" may be analyzed in the light of at least three major representative formulations in social science literature: social locations, behavior, and expectations. These elements are the major foci of this paper.
Keywords: Local government; Public administration; Public officers; Rural development; Political development